Structural and morphological study of mechanochemically synthesized crystalline nanoneedles of Zr-doped carbonated chlorapatite - Nasiri-Tabrizi, B.; Zalnezhad, E.; Pingguan-Murphy, Belinda; Basirun, Wan Jefrey; Hamouda, A.M.S.; Baradaran, S. (Elsevier, 2015)
Nanosize Zr-doped carbonated chlorapatite (n-ZCCA) was developed as a novel bioceramic by a ball milling process. Results showed that the microstructural characteristics of the product were affected significantly by the degree of substitution and subsequent annealing at 800 degrees C for 1 h. In the absence of zirconium, mechanical activation for 3 h resulted in the formation of carbonated hydroxyapatite (CHA). With the addition of various amounts of zirconium, nanosize Zr-doped carbonated chlorhydroxyapatite (n-ZCCHA) and n-ZCCA were formed as a result of progressive mechanochemical reactions. From the HR-TEM images, the preferential substitution of Zr onto the ac or bc chlorapatite crystal facets (rich in calcium ions) led to a c-axis oriented crystal growth of crystalline nanoneedles with an average size of around 40-60 nm in length and 10-20 nm in width. (C) 2015 Elsevier B.V. All rights reserved.